If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17t + -19t + -4 = 4 Reorder the terms: -4 + 17t + -19t = 4 Combine like terms: 17t + -19t = -2t -4 + -2t = 4 Solving -4 + -2t = 4 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -2t = 4 + 4 Combine like terms: -4 + 4 = 0 0 + -2t = 4 + 4 -2t = 4 + 4 Combine like terms: 4 + 4 = 8 -2t = 8 Divide each side by '-2'. t = -4 Simplifying t = -4
| 2a^2+8-(a-5+5a^2)-9a= | | -3x+6.2=-5.8 | | 5a+5(1-a)=a+8 | | 4y+7=-7 | | 3x-6+3x=-36 | | -3y=-3x-3 | | 83-x=-33 | | 2z+8=-12+z | | -4x=76 | | -9=-8.6+x | | -33x=83 | | 7-2z=13 | | 3z-3+z=23 | | -23-11-(-7)+(-25)= | | 6x-11y=8 | | 15y=-4+5x | | t+12(3t-t^2)= | | -3+6.2=-5.8 | | 1.2x-1=2(1.6x+1.5) | | 83x=-33 | | 50x^2-2= | | 81t-64t=0 | | .3x-x=-16 | | .3x-x=16 | | f(s)=s^2(s^2+2) | | 3x-(6-2x)=39 | | 3z-6=z+4 | | .26d=.104 | | 7.46=2*3.14*r | | x-1.34=9 | | 7(z-2)=3(z-1) | | 0.56+0.46t=4.36t-1.00 |